Postmodernisme dan Pendidikan Agama: Membedah Tantangan Post-Truth dalam Kurikulum Pendidikan Islam - Taufiq; Ishomuddin; Khozin (SITASI: Journal of Islamic Studies and Inclusive Education, 2026)
This article examines the challenges facing Islamic education in the context of the strengthening philosophical paradigm of postmodernism and the social phenomenon of post-truth, characterized by the relativism of truth, the crisis of scientific authority, and the dominance of digital media. This shift impacts Islamic education, particularly in the aspects of epistemology, curriculum, and institutional roles. This research employs a qualitative-descriptive approach with philosophical and critical analysis of literature related to postmodernism, Islamic epistemology, post-truth, and education in Indonesia. The findings indicate that Islamic education faces a dilemma between maintaining the normative truth of revelation and responding to social-digital relativism. The curriculum, which remains normative-transmissive, is also insufficiently responsive to these changes, resulting in the weak critical thinking skills and epistemic literacy of learners. The novelty of this research lies in the synthesis of bayani, burhani, and irfani epistemologies with the concept of epistemic literacy to respond to post-truth challenges in Islamic education. This framework is directed toward strengthening learners' abilities to verify information, think critically, and remain grounded in the values of revelation as well as moral-spiritual principles. Furthermore, Islamic educational institutions are positioned as institutions that play a role in producing, verifying, and directing Islamic knowledge in the digital space. Thus, the reconstruction of epistemology, curriculum, and institutions is essential so that Islamic education remains relevant in the post-truth era.